UPAYA PENCEGAHAN FUNDAMENTALISME AGAMA DALAM PERSPEKTIF HINDU - Warta, I Nyoman (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
Grounding fundamentalism in the perspective of Hinduism is a complex issue and requires in-depth analysis of the basic principles of universal Hindu teachings and how they are applied in modern life. Fundamentalism in the context of religion usually refers to rigid efforts to maintain a literal interpretation of the Holy Scriptures and traditions that have become traditional in life. In Hinduism, which has many branches of philosophy, beliefs, and practices that vary in diversity, the concept of fundamentalism faces its own challenges. Hindu teachings are inherently pluralistic, with texts such as the Vedas, Upanishads, Bhagavad Gita, and various commentaries from Hindu philosophers, offering room for broad and flexible interpretations. Thus, efforts to apply fundamentalism tend to be at odds with the essence of Hindu teachings which are tolerant and adaptive to changes in the times. This paper aims to examine how the concept of fundamentalism can emerge in the context of Hinduism, what factors influence its journey, and its impact on pluralism and harmony between religious communities in society. Through a historical, theological, and sociological approach, hopefully this article can provide insight into the dynamics between pluralistic Hindu teachings and fundamentalist tendencies that may develop in certain situations and will certainly face challenges that are not easy. From a Hindu perspective, efforts to avoid fundamentalism require a comprehensive strategy based on the basic principles of Hinduism, including tolerance, plurality, living in harmony, diversity in diversity, wasudhaiwa kutumbhakam, respecting humanism and ahimsa (non-violence). As an inclusive religion, Hinduism recognizes that there are various paths to spiritual freedom and universal truth. Seeing this reality, by understanding, practicing and thoroughly practicing the teachings of the Vedas to prioritize the importance of community peace and openness to differences, is one way to anticipate fundamentalism in Hinduism. The basis for preventing radicalism and extremist views are religious values ​​that emphasize the principles of tolerance, mutual respect, and respect for cultural and religious diversity. In addition, interfaith cooperation and dialogue are important means to foster a shared understanding of peace and harmony. In this sense, Hinduism offers a strong intellectual and ethical foundation to neutralize radicalism in all forms by promoting human brotherhood and universal morality.